Vigilante : behind the scenes of the Batman films [videorecording (DVD)] - Gutierrez, Roly; Somoza, Miguel (Dreamscape Media, LLC, 2022)
With the rise in superhero media, this documentary relives the rise and reign of the vigilante over the last eight decades in this dynamic biography of the Batman.